AlGaN-based metal–semiconductor–metal photodiodes fabricated with nonplanar structure geometry for ultraviolet light detection. (15th June 2023) - Tsai, Chia-Lung; Wang, Tong-Wen; Manjunatha, S.N.; Sharma, Mukta; Das, Atanu; Chen, Chia-Wei; Zhang, Jin-Rong; Chen, Yi-Shian; Ko, Sun-Chien
Abstract: Based upon GaN-on-Si wafers with a Al0.24 Ga0.76 N/AlN/GaN heterostructure, metal–semiconductor–metal photodetectors (MSM PDs) with nonplanar structure geometry are proposed for ultraviolet (UV) light detection. Although the presence of a highly conductive two-dimensional electron gas (2DEG) channel in the Al0.24 Ga0.76 N/AlN/GaN heterostructure is beneficial for realizing a high-electron-mobility transistor with a drain current of 600 mA/mm and a transconductance of 96 mS/mm, a high dark current is also observed in Schottky-barrier based MSM PDs. Using the nonplanar structure design for the MSM PDs (i.e., one Schottky contact formed on the top surface of the AlGaN mesa while the other is on the GaN buffer) achieves a significant decrease in PD's dark current (<6 × 10 −10 A). In addition, an anomalous increase in dark current of the proposed MSM PDs was found at forward bias, which could be attributed to the reduced potential barrier of the electrons in 2DEG and/or the lowering of the Schottky barrier height by hole trapping at the metal/semiconductor interface. Due to the improved signal to noise ratio and increased dissociation of the photogenerated carriers at the reverse junction (i.e., the reversely biased Schottky contact), the proposed MSM PDs operating at reverse bias exhibit enhanced UV photoresponsivity at λ < 360 nm. In addition to being used for UV light detection, these MSM PDs with a 3-dB bandwidth of 29.6 Hz are also useful for potential optical communications applications.